Analisis Pengaruh Pelayanan, Promosi, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Di Matahari Departement Store (studi Kasus Matahari Departemen Store Solo, Cabang Singosaren) - Nugroho, Ardiansyah Bayu; , Sri Murwanti, SE. M.M (2016)
The aim of this study was to determine the effect jointly or in partial, Service, Promotion, Product Quality, Price on Purchasing Decisions in Matahari Department Store Singosaren Solo. This research is descriptive quantitative questionnaire as a data collection tool that is analyzed using data proces sing software SPSS for Windows version 22. The samples were carried out using non-probability sampling through accidental sampling method, the number of respondents used was 100 respondents. The result is either jointly or individually variable Care, Promotion, Product Quality, Price on Purchasing Decisions in Matahari Department Store Singosaren Solo. The survey results revealed that the price variable is a variable that gives the most influence on purchasing decisions.